2017
DOI: 10.5380/rf.v46i4.44199
|View full text |Cite
|
Sign up to set email alerts
|

Perfil Dos Incêndios Florestais Em Unidades De Conservação Brasileiras No Período De 2008 À 2012

Abstract: ResumoOs incêndios florestais estão entre as principais ameaças à biodiversidade. Mesmo em áreas especialmente protegidas, a ameaça é constante. Diante disto, o objetivo deste estudo foi conhecer o perfil dos incêndios florestais nas Unidades de Conservação (UCs) federais no Brasil no período de 2008 a 2012, a fim de se fornecer informações para subsidiar a tomada de decisões de forma mais segura e confiável. Para a determinação deste perfil, foram compiladas as informações do banco de dados do Sistema Naciona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1
26

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 18 publications
0
12
1
26
Order By: Relevance
“…In these areas, the traditional communities, whose subsistence activities are based on extractives, subsistence farming, and raising small animals, are allowed [86]. The study of Torres et al [87], using a Brazilian firefighters database, revealed that the fire use for land clearing is the main cause of wildfires in the CUs. Incendiarism was the second recurrent cause of wildfires in CUs.…”
Section: Fire Occurrence and Land Tenure Relationshipmentioning
confidence: 99%
“…In these areas, the traditional communities, whose subsistence activities are based on extractives, subsistence farming, and raising small animals, are allowed [86]. The study of Torres et al [87], using a Brazilian firefighters database, revealed that the fire use for land clearing is the main cause of wildfires in the CUs. Incendiarism was the second recurrent cause of wildfires in CUs.…”
Section: Fire Occurrence and Land Tenure Relationshipmentioning
confidence: 99%
“…A forest fire is any fire without control and has destructive power which occurs in vegetation, being initiated by human or natural actions (TETTO et al, 2015;EUGENIO et al, 2016;MOTA et al, 2019). These situations enhance the formation of forest fragments, the destruction of biodiversity, material goods and even human lives, increase erosion rates, soil compaction, runoff, and consequently silt up water bodies (HERAWATI et al, 2011;MORA et al, 2016;MURILLO et al, 2016;VAN ECK et al, 2016;TORRES et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the establishment of fire monitoring, control and prevention strategies are extremely important. For this, forest fire statistics are a fundamental tool (PEREIRA et al, 2014), since it helps to define the main sites and times of occurrence and causative agents (TORRES et al, 2016). However, one limiting factor to these statistics is often the lack of information and standardization of data on forest fires, being hotspots an alternative to help decision making.…”
Section: Introductionmentioning
confidence: 99%